Optimalisasi Penerapan ICT dan Pendekatan Sainstifik Dalam Pembelajaran - Dian Rahadian; Yuniar Purwanti; Siti Husnul Bariah; Kuntum An Nisa Imania; Iman Nasrulloh; Dudi Suprihadi (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
Technological advances are currently experiencing very rapid developments marked by the emergence of information and communication technology which is increasingly sophisticated and innovative from year to year. The field of education is one of the most important fields to pay attention to for the fulfillment of qualified human resources to advance the development of a nation. The purpose of this training is to provide understanding and skills to teachers in managing learning by using information and communication technology in a scientific approach. The training participants consisting of teachers at the MI, MTs, and MA education levels gave a positive response which was indicated by the enthusiasm of the number of participants who took part in the training and questions and answers during the training.